Has IFRSs improves predictions of future cash flows? evidence from Malaysia - Abdullah Atqa, Asna; Lee, Kok Hwa; Mohd Saleh, Norman (Universiti Malaysia Sarawak * Faculty of Economics and Business, 2019)
The International Financial Reporting Standard (IFRS)’s conceptual framework and the Financial Accounting Standards Board (FASB)’s conceptual framework state that future cash flows prediction is one of the key objectives of financial reporting. Given the use of cash flows as a performance measure besides earnings, the effectiveness of IFRS in satisfying this financial reporting objective, increases in its importance. Hence, this study seeks to investigate whether the adoption of IFRS (or locally known as the Malaysian Financial Reporting Standard (MFRS)) in Malaysia since the year 2006 improves the predictability of future cash flows of Malaysian public listed firms. 4,068 firm-year data of Malaysian public listed companies in year 2004 to 2012 is analysed. The results show that current cash flows under IFRS regime significantly predict future operating cash flows. Despite the non-significance of net income and current accruals under the IFRS regime, the Malaysian companies show relatively high acceptance of the convergence of accounting standards towards IFRS. Other control variables show mixed results. This study provides insights into the benefits of regulation such as the IFRS, with policy implication on standard setters and financial reporting regulators.